2019
DOI: 10.1111/1475-6773.13153
|View full text |Cite
|
Sign up to set email alerts
|

Exploring the association of care fragmentation and patient ratings of care quality: A mediation analysis of women Veterans’ experience with VA care

Abstract: Objective To examine the relationship between care fragmentation and patient ratings of care quality and identify potentially actionable mediators. Data Sources/Study Setting 2015 telephone survey of 1395 women Veterans with three or more visits in primary care and/or women's health care in the prior year at 12 Veterans Affairs (VA) medical centers. Study Design Cross‐sectional analysis. Data Collection/Extraction Methods We operationalized lower care fragmentation as receiving VA‐only care versus dual use of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
18
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(19 citation statements)
references
References 39 publications
1
18
0
Order By: Relevance
“…ontinuity of care, a core principle of high-quality primary care, is associated with improved quality of care [1][2][3][4][5] and patient outcomes, [6][7][8][9][10] including greater delivery of preventive services and lower rates of hospitalization and emergency department visits, as well as lower costs of care for chronic illness. [8][9][10] Based on this evidence, strengthening the relationship between patients and primary care physicians (PCPs) has been a centerpiece of delivery reform efforts targeting highcost and uncoordinated care.…”
mentioning
confidence: 99%
“…ontinuity of care, a core principle of high-quality primary care, is associated with improved quality of care [1][2][3][4][5] and patient outcomes, [6][7][8][9][10] including greater delivery of preventive services and lower rates of hospitalization and emergency department visits, as well as lower costs of care for chronic illness. [8][9][10] Based on this evidence, strengthening the relationship between patients and primary care physicians (PCPs) has been a centerpiece of delivery reform efforts targeting highcost and uncoordinated care.…”
mentioning
confidence: 99%
“…Furthermore, it is critical that social scientists examine veterans' experiences with, for example: (1) coordinating care among different healthcare providers; (2) using different types of insurance (cf. Chanfreau‐Coffinier et al 2019); and (3) the care options available to aging rural veterans as they plan for and enter retirement.…”
Section: Discussionmentioning
confidence: 99%
“…In a recent case study of urban women veterans (Evans et al 2019:25) which explored why women veterans do not use VA healthcare, reasons identified were related to women's perceptions of the accessibility, appropriateness, and acceptability of the VA environment and services. Research by Chanfreau‐Coffinier et al (2019), which also examined perceptions of healthcare among women veterans, found that women's views of the quality of care was affected by their use of different healthcare sources—VA and non‐VA. Specifically, higher quality ratings were associated with less fragmented healthcare use.…”
Section: Introductionmentioning
confidence: 99%
“…For Equations () and (), the volume of services serves as a dependent variable in Equation () and an independent variable in Equation (). This method is also known as mediation analysis, where the direct effect (ie, the effect of labor and capital inputs on quality in Equation ()) and the indirect effect of independent variables (ie, the effect of labor and capital inputs on quality mediated through Equation () and volume term in Equation ()) can be estimated separately 54‐56 . Appendix Figure presents a conceptual path diagram for this mediation analysis.…”
Section: Methodsmentioning
confidence: 99%